Analysis Descriptive of Anosmia and Dysgeusia in SARS CoV-2 Patients: Overview of Epidemiology, Pathogenesis, Prognosis, and Treatment Options - Muhammad, Izbikavik; Prasetyo, Yohannes Eddy; Nur, Rifqi Misbahuddin (Universitas Muhammadiyah Malang, 2023)
Introduction: SARS CoV-2 (COVID-19) is a respiratory infectious disease whose cause has been identified as the seventh type of the coronavirus family that attacks humans. Common symptoms among patients with COVID-19 include fever, dry cough, shortness of breath (dyspnea), muscle aches (myalgia), confusion, headache, sore throat, rhinorrhea, chest pain, diarrhea, nausea / vomiting, conjunctival congestion, nose. congestion, sputum production, fatigue (malaise), hemoptysis, and shivering. However, the spread of COVID-19 infection has shown new symptoms of the disease: patients with dysfunction of smell, taste and indigestion. Methods: Literature review by taking libraries from 34 journals and 2 textbook. The journal obtained from the Google, NCBI and Pubmed search engine, as well as processing research materials into new information related to the research objectives. Results: One hypothesis currently developing is that SARS-CoV-2 will cause olfactory changes through direct access and damage to the CNS through its penetration by the cribriform plate. Another hypothesis that is also developing suggests direct viral damage to olfactory cells and taste receptors. Glial cells, neurons, and the oral cavity present the ACE-2 receptor which appears to be a mechanism of cell invasion by viruses. Conclusion: People who have lost their smell or taste are six times more likely to become positive for COVID-19. Likewise, people who have anosmia have a 10-fold higher chance of being diagnosed with COVID-19. Taste and smell disorders with ageusia have a 10 times higher chance of catching COVID-19.